Primary tracheo‐bronchial adenoid cystic carcinoma: A surgical series with literature review - Kaouther Ben Amara; Imen Bouassida; Rahma Ayadi; Mariem Affes; Amina Abdelkbir; Mahdi Abdennadher; Salma Ben Othmen; Ayda Ayadi‐Kaddour; Hazem Zribi; Adel Marghli (Respirology Case Reports)
Abstract Tracheo‐bronchial adenoid cystic carcinoma (TBACC) is a rare disease. Its treatment is mainly surgical. We herein describe the clinical and para‐clinical varieties of TBACC as well as their surgical treatment and prognosis. We conducted a retrospective study of eight patients operated on between 1994 and 2022 and whose definitive pathological examination concluded with primary TBACC. There were three men and five women with an average age of 44 years. The bronchoscopy found a budding formation reducing the tracheal lumen at the cervical (two cases), middle (two case) and distal trachea and carina (four cases). Bronchial anastomosis resection and sleeve pneumonectomy were the most common procedures. Surgical resections R0 were achieved in five patients. Surgery followed by adjuvant radiotherapy was performed in two patients with incomplete surgical resection R1. The overall survival for all patients with primary ACC was 72% at 5 years. TBACC is a rare and low‐to‐moderate grade malignant tumour. The choice of the surgical procedure and the appropriate approach is challenging to obtain a promising prognosis.